Level of satisfaction of mothers with the obstetric care during childbirth and puerperium of the Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2024)
In order to determine the level of satisfaction of mothers with obstetric care during labor and puerperium in the Department of Obstetrics and Gynecology of the Central University Hospital Dr. Antonio María Pineda during August-September 2022, a descriptive cross-sectional study was carried out with 50 mothers whose average age was 26.2 ± 7.48 years, 60% were single, 72% had secondary education, 54% were housewives and 60% were from rural areas. In addition, 44% were primiparous, 84% had a full-term pregnancy and in 58% of cases the delivery was vaginal. Eighty-eight percent of the patients were very satisfied with the information received in the delivery room and all were satisfied with the number of professionals who attended them during delivery; 94% were indifferent to the analgesia and comfort measures after birth. Regarding postpartum care, 96% of the patients were very dissatisfied with the time the nurse spent helping to feed their baby and 98% were very satisfied with the number of physicians who attended them. Regarding newborn care 78% were very satisfied about finding help when needed; 98% were satisfied with positioning the baby during feeding and 62% were dissatisfied with knowing what to do when the baby choked. Regarding logistics and environment, 98% and 92% of the patients were dissatisfied with the quality of the food and the accessibility of what they needed, respectively. Regarding the overall level of satisfaction, 60% were completely satisfied, 38% moderately satisfied and 2% not at all satisfied. Patient satisfaction is an indicator of the quality of health care, especially during obstetric care.